PENGARUH PROMOSI TERHADAP PENGETAHUAN PRODUK DAN LOYALITAS KONSUMEN PADA UNIT USAHA SYARI’AH PT. BANK NTB - Muhdim Muhdim (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2016)
The purpose of this study was to (1) To determine the significance of partial effect of Individual Characteristics, Leadership, Work Environment, Compensation and Career Prospects of the Work Motivation Head of the village in the district of East Lombok Keruak. (2) To determine the significance of the simultaneous effect of Individual Characteristics, Leadership, Work Environment, Compensation and Career Prospects of the Work Motivation Head of the village in the district of East Lombok Keruak. (3) To find out which of the factors Individual Characteristics, Leadership, Work Environment, Compensation and Career Prospects that have a dominant influence on work motivation Head of the Village in the district of East Lombok Keruak. Methods used are causal research. The data collection was conducted using questionnaires given to 90 respondents. Analysis of data using multiple linear regression analysis. The results showed that (1) There is a significant influence on the Simultaneous Individual Characteristics, Leadership, Work Environment, Compensation and Career Prospects of the Work Motivation Head of the Village in the District Keruak East Lombok. (2) There is a significant influence on the Partial Individual Characteristics, Leadership, Work Environment, Compensation and Career Prospects of the Work Motivation Head of the Village in the District Keruak East Lombok. (3) Compensation has a dominant influence on work motivation on the District Head of Village Affairs Keruak East Lombok. Keywords: Individual Characteristics, Leadership, Work Environment, Compensation, Career Prospects, Work Motivation